PID Neural Network Based Speed Control of Asynchronous Motor Using Programmable Logic Controller - (:unkn) unknown (UNIV SUCEAVA, FAC ELECTRICAL ENG, 2011)
This paper deals with the structure and characteristics of PID Neural Network controller for single input and single output systems. PID Neural Network is a new kind of controller that includes the advantages of artificial neural networks and classic PID controller. Functioning of this controller is based on the update of controller parameters according to the value extracted from system output pursuant to the rules of back propagation algorithm used in artificial neural networks. Parameters obtained from the application of PID Neural Network training algorithm on the speed model of the asynchronous motor exhibiting second order linear behavior were used in the real time speed control of the motor. Programmable logic controller (PLC) was used as real time controller. The real time control results show that reference speed successfully maintained under various load conditions.
Keywords: control; neural network; PID; PIDNN; PLC; SYSTEM